A matter of distribution: APC logic against consortial funding mechanism - Eve, Martin Paul (Septentrio Conference Series, 2017)
Watch the VIDEO here. Article and Book Processing Charges have become one of the most common mechanisms for paying for gold open access. It is envisaged that this looks like a “flip” from a purchase model to a service model. However, the change in distribution that is effected in such a transition is substantial. In this talk, I will examine the economic distributions of APC mechanisms as opposed to consortial funding. I take examples from the monograph and journal publishing spaces. I also examine the distributional changes from the UK’s Research Excellence Framework’s proposed mandate for monographs. I finally then ask what the actual costs are in running a small scholarly publisher and how the distributional changes implied by APCs – a move from fixed costs to unit costs – hit such entities. In all, this talk aims to provoke discussion about alternative models and mitigating strategies for collectively underwriting open access.